PENGENALAN PROGRAM STUDI MATEMATIKA DALAM KONDISI PANDEMI COVID-19 - Novita Eka Chandra; Siti Alfiatur Rohmaniah; Mohammad Syaiful Pradana; Awawin Mustana Rohmah; Siti Amiroch (LPPM Universitas Islam Darul 'Ulum Lamongan, 2021)
The increasingly high spread of Covid-19 pandemic cases has an impact on the field of education, especially new student admissions. In accordance with government policy, activities related to education were changed to online, so that the mathematics study program held promotional activities through online. This activity is focused on accepting new students online during the Covid-19 pandemic. Methods for implementing the activities include making materials for introducing mathematics courses through websites and social media, making flyers and banners, making profile videos, and conducting webinars. The results of the introduction of the mathematics study program in the context of socializing online new student admissions during the pandemic were very good, where more than 60% of the participants stated that the activities were very interesting and satisfying.